2016
DOI: 10.24252/eternal.v21.2016.a7
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Collaborative Strategy Reading (Csr) and Its Effects on Students’ Reading Comprehension

Abstract: : This research aimed to find out: (1) the students' attitude toward CSR in teaching-reading comprehension and (2) the role of CSR and its affects on students' reading comprehension. This study was experimental which involved two groups: experimental and control groups. The research was conducted at Madrasah Aliyah Negeri MAN 1 Makassar, South Sulawesi with 40 students as respondents. The instruments of data collection were pre-test, treatment, post-test, and questionnaire. The reading test was administered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…The result of the present study which shows that there was an increase of the mean scores in the students' reading comprehension is in congruence with the findings of Rahman (2015) on the effects of Collaborative Strategic Reading in the Indonesian students' reading comprehension. In her study, it showed that there was a significant improvement in the quality of the students' reading comprehension in the experimental group while the quality of students' reading comprehension in the control group was increased.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The result of the present study which shows that there was an increase of the mean scores in the students' reading comprehension is in congruence with the findings of Rahman (2015) on the effects of Collaborative Strategic Reading in the Indonesian students' reading comprehension. In her study, it showed that there was a significant improvement in the quality of the students' reading comprehension in the experimental group while the quality of students' reading comprehension in the control group was increased.…”
Section: Resultssupporting
confidence: 90%
“…The significant result of this study is parallel to the previous research of Rahman (2015) showing the students' attitude toward the use of CSR in reading classroom. The implementation of Collaborative Strategy is remarkably good because most of the students' attitudes get high to very high score and only a few of them gets enough score.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In this research, it was found that collaboration skills were taught in some English literacy activities. The implementation of collaborative strategy reading was responded positively by students (Rahman, 2015). It could improve students reading comprehension significantly.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the application of this strategy was also found to be beneficial for teachers because it made it easier for teachers to guide students to work cooperatively in a team of five or more depending on the number of students in the class. In line with research conducted by [5] it is stated that this CSR strategy has proven to be successful in improving students' ability to understand the content of reading texts and enriching students' vocabulary in interpreting the author's intentions in English reading texts. This is supported by the findings from [6] that this strategy can help students develop their ability to work together or collaborate considering that a discussion group will make the reading comprehension process more comfortable and easier.…”
Section: Introductionmentioning
confidence: 56%